High Prevalence of Bovine Viral Diarrhea Virus-1 in Sheep Abortion Samples with Pestivirus Infection in Turkey - Bulut, Hakan; Sozdutmaz, Ibrahim; Pestil, Zuleyha; Abayli, Hasan; Sait, Ahmet; Cevik, Aydin (Univ Agriculture, Fac Veterinary Science, 2018)
The aim of this study is the detection of prevalence of bovine viral diarrhea virus-1 (BVDV-1) in sheep abortion samples in Turkey. For this purpose, initially, the detection of pestiviruses, bluetongue virus (BTV) and akabane virus (AKAV) was performed by reverse transcription-polymerase chain reaction (RT-PCR) from the aborted sheep fetus specimens. Then, for differentiation of pestiviruses, further investigations were carried out from the pestivirus positive samples. Pestiviruses RNAs were detected from 98 (24.74%) of 396 aborted fetus samples collected from 13 provinces in Turkey. By using border disease virus (BDV) and bovine viral diarrhea virus (BVDV) specific primers, 58 (59.18%) of pestivirus positive 98 samples were detected as BDV and the remaining 40 (40.81%) were found as BVDV with RT-PCR. According to the results, BVDV RNAs were detected from 10.10% (40/396) of aborted fetus specimens. By sequencing and phylogenetic analysis of BVDV positive four samples, BVDV-1 was identified as the genotype of BVDV. The BTV and AKAV genome were not detected from the 396 aborted samples tested in this study. In conclusion, there's a high ratio of BVDV-1 among sheep abortions in Turkey. According to this study results, we think that the high prevalence of BVDV in sheep abortion cases may be important for the control programme against persistent BVDV infections. (C) 2017 PVJ. All rights reserved
Keywords: Abortion; Bovine viral diarrhea virus; RT-PCR; Sequencing; Sheep